STRATEGI MEMBANGUN RUMAH TANGGA YANG HARMONIS PADA PASANGAN BURUH TANI (Studi di desa Mojosari kecamatan Kras kabupaten Kediri ) - Abdurrochman (CV. KAMPUS AKADEMIK PUBLISING, 2024)
The strategy of building a harmonious household is very important. In every household there are differences to achieve a harmonious household, there must be criteria for a harmonious household, strategies for building a harmonious household, factors inhibiting and supporting factors for harmony and equality based on the public and domestic domains. This research is empirical research, with a qualitative approach, namely an approach that produces written or verbal data from the people interviewed. Data collection was carried out using interview, observation and documentation methods with farm workers in Mojosari village, Kras sub-district, Kediri regency.These results show that:Farm workers' efforts to create household harmony by complementing each other, giving in to each other, being open to each other honest with each other in all matters, respecting each other, carrying out obligations ordered by Allah, educating wives and children., In a household there are definitely factors that hinder household harmony, including: Parents or in-laws interfering, being selfish towards each other, not understanding each other towards family members.Meanwhile, the supporting factors are the presence of family members who always provide assistance, children who understand the family situation and the condition of the house which is a motivation to provide a suitable place for the family.